Overview of Tuberculosis Case Finding in Kulon Progo Regency, 2021-2023 - Sunaini, Ainun; Riswandi, Iwan; Indriani, Citra; Sugiarto (BKM Public Health and Community Medicine, 2024)
Purpose: Tuberculosis (TB) remains a major health problem in Kulon Progo Regency. Case finding is one of the key efforts to control TB. The purpose of this study is to provide an overview of TB case finding in Kulon Progo Regency for the last three years (2021-2023). Methods: This study used a descriptive design using surveillance data from the Tuberculosis Information System (SITB) of the Health Office. Analysis by place and person was presented in tables and graphs. Results: There were 216 cases in 2021 (26% of the target), 317 cases in 2022 (32.6%) and 269 cases (45%) in 2023. Males accounted for 58.6% of the total cases. Most TB cases were found at ages 55-65 years (18.6%), ages >65 years (17.2%), and ages 45-54 years (14.9%). The highest number of TB cases with a total of 70 cases was found at the Wates Health Center. One of the strategies for case finding is through early detection of Contact Investigation (CI). In 2021, CI only reached 55.6% of the total cases that were CI (71.8% of the targeted number of contacts), in 2022 it increased to 72.5% of the total cases with the number that had been CI (51.7%). However, in 2023 the number of CI cases decreased to only 63.19% with 51.7% of contacts. This achievement is still below the target, which is 90% of TB cases should be contact investigated. Discussion: The average contact investigation per case is still below the WHO recommendation of 8 contacts per case. Cross-sector collaboration affects the success of early TB detection. Conclusion: TB case-finding efforts need to be increased to achieve predetermined targets. One of the efforts that can be made is the intensification of active contact investigation of TB patients in Kulon Progo Regency.